The Effect of Influencer Marketing on Gen Z Purchasing Intentions in Emerging Economies - Ida Bagus Surya Dharma; Hengky Hengky; Lim Lee Ching; Lim Shi Ni; Lim Shu Zhen; Lim Zhi Yee; Nsobundu Ugochukwu Brayn; Sehrish Syed Ilyas; Kok Ban Teoh; Odebunmi Abayomi Tunde; Gai Sin Liem; Friday Ogbu Edeh; Rupesh Kumar Sinha (Asia Pacific Journal of Management and Education (APJME), 2024)
The emergence of influencer marketing in developing countries has been facilitated by Generation Z's use of social media. This study's goal is to discover how influencer marketing will affect Gen Z consumers' purchasing intentions in Indonesia, Malaysia, India, and Nigeria. In this study, the data were examined utilizing descriptive, reliability, correlation, and regression analysis employing quantitative research and IBM SPSS Statistics 26. The data collection method was carried out online with a group of 150 individuals from the Gen Z demographic participating. The study highlights that perceived influencer credibility, product-influencer relevance, perceived expertise, and trustworthiness significantly impact Gen Z's purchasing intentions in Indonesia, Malaysia, India, and Nigeria. Authentic, credible influencers who align with a brand's image strengthen consumer trust and purchase intent. Marketers should prioritize collaborations with influencers known for genuine, relatable, and expert content, fostering deeper engagement and brand loyalty. While peers' reviews showed less impact, further research could explore Gen Z's evolving approach to social proof.